2017
DOI: 10.1097/moh.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of β-amyloid peptide with fibrinogen and coagulation factor XII may contribute to Alzheimer's disease

Abstract: Purpose of the Review To review the evidence that the Alzheimer peptide β-amyloid (Aβ) interacts with the blood coagulation system and influences the pathophysiology of the disease. Recent findings That Aβ can interact with fibrinogen and blood coagulation Factor XII and trigger ischemia and inflammation. Summary Aβ interacts with fibrinogen and FXII. These interactions can lead to increased clotting, abnormal clot formation, persistent fibrin deposition, and generation of pro-inflammatory molecules. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Recent studies (e.g. Ahn et al ., , , ; Cortes‐Canteli et al ., , ; Cortes‐Canteli & Strickland, ; Zamolodchikov et al ., ; Zamolodchikov & Strickland, ) have highlighted its interaction with Aβ peptides in Alzheimer's disease. Here, it is important to recognise that the faster kinetics of a given amyloidogenic process (such as fibrin formation) might accelerate the kinetics of a different amyloid with which it happens to interact, and that this could have important implications for the initiation of overt disease.…”
Section: Step 6: Induction Of Fibrin Amyloid Formation By ‘Iron’ Lpsmentioning
confidence: 99%
“…Recent studies (e.g. Ahn et al ., , , ; Cortes‐Canteli et al ., , ; Cortes‐Canteli & Strickland, ; Zamolodchikov et al ., ; Zamolodchikov & Strickland, ) have highlighted its interaction with Aβ peptides in Alzheimer's disease. Here, it is important to recognise that the faster kinetics of a given amyloidogenic process (such as fibrin formation) might accelerate the kinetics of a different amyloid with which it happens to interact, and that this could have important implications for the initiation of overt disease.…”
Section: Step 6: Induction Of Fibrin Amyloid Formation By ‘Iron’ Lpsmentioning
confidence: 99%
“…Notably, brinogen and its cleavage products are known to contribute to in ammation in the CNS by a variety of mechanisms including microglial activation [77,78], neuronal damage [79], interactions with beta-amyloid [80], and disruption of the blood-brain barrier [81]. In fact, alterations in CNS brinogen biology have been implicated in the pathogenesis of neurological, neurocognitive, and psychiatric disorders including multiple sclerosis [82], traumatic brain injury [83], Alzheimer's disease [78,84], and depression [85]. Likewise, coagulation factor V, a central mediator of hemostasis, has been previously linked to delirium pathogenesis [33].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found an increase in plasminogen, brinogen and kininogen. In AD, plasminogen was found to colocalize with Aβ plaques [37], while brinogen was capable of enhancing Aβ aggregation and brillization, causing impairment in AD [48,49]. Patients with higher levels of plasma brinogen and plasminogen modulating neuroin ammation had worsening cognitive decline and Aβ deposition [37,50,51].…”
Section: Discussionmentioning
confidence: 99%